Price Risk Control of Natural Resource Commodities through Behavioral Finance Analysis: An Information Transfer Perspective - Zehui Liu (Discrete Dynamics in Nature and Society)
To fully understand the market price volatility mechanism of natural resource commodities (NRCs), and control the price risks of NRCs, it is important to deeply analyze how NRC price is affected by uncertain risk factors, such as supply risk, demand risk, macroscopic price risk, political price risk, policy price risk, seasonal price risk, and sudden price risks. The theory of behavioral finance can establish a transaction decision-making model more in line with the actual market situation. Therefore, this paper explores the price risk control of NRCs from the perspective of financial theories. Firstly, the authors empirically examined the specific impacts of uncertain risk factors on NRC price, and the directions of the impacts. Next, the price volatility and transaction risks of NRCs brought by information transmission were analyzed, following by the construction of an information transmission model for NRC trading market. After that, a dynamic price model was built for NRCs based on the theory of behavioral finance. Finally, the effectiveness of the proposed model was verified through experiments.